Documentation of Wild Decorative Plants of Tribhuvan Highway in Makawanpur District, Nepal - Thakur, Chandrakala; Parajuli , Raghu Ram (Journal of Plant Resources, 2024)
The present study highlights the exploration of wild decorative flowering plants which were documented on the roadside of the Tribhuvan highway from Hetauda to Tistung. This study area consists of tropical, sub-tropical and temperate vegetation types. This study was carried out during the year 2021-2023 and several field visits were performed. Plants were collected from the 17 transect line starting from Hetauda to Tistung Botanical Garden, Tistung. Each transect line was 200 meters in length measuring from the center of the road to 100 m left and 100 m right sides of the Tribhuvan Highway. From this survey altogether 120 species of wild ornamental plants belonging to 89 genera and 47 families were recorded. The most dominant family in terms of species richness was Orchidaceae having 30 species, followed by Fabaceae with 13 species. In terms of genera, Dendrobium  and Coelogyne were  the most dominant genera having  seven species in each. Similarly, in analysis based on life form, the herb category was largest containing 61 species, followed by shrub with 31 species. Climber and tree consisted of 16 and 12 species respectively. The result also depicted that the diversity along the Tribhuvan Highway (Hetauda to Tistung) had an abundance of wild ornamental plants which comprises a wide range of diversity in terms of taxa, habit and life forms. This study suggests that this research work will be helpful for students, researchers and people who keep an interest in the gardening of indoor plants and outdoor landscape practices. Furthermore, in order to protect, conserve and perpetuate these plants, the florists, horticulturists, nurserymen and concern authorities are advised to introduce some potential native wild ornamental plants for the domestication.